(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2025)
Mental health has emerged as a critical global issue, with individuals increasingly experiencing stress, anxiety, and fatigue—conditions that underscore the need for environments conducive to psychological restoration and relief from daily pressures. Architectural design that emphasizes therapeutic qualities offers the potential to address these mental health challenges by fostering spaces that support psychological well-being. Recent studies have demonstrated that the application of therapeutic architectural principles within the built environment can significantly influence both the physical and mental health of its users. This research addresses a gap in the current discourse by examining the integration of therapeutic concepts within the architectural design of retreat houses. While prior studies have independently explored the phenomenology of spiritual retreats and architectural strategies with psychological impact, limited research has investigated the intersection of these domains. Accordingly, this study focuses on the relationship between architecture and therapeutic concepts, specifically through the lens of theoretical exploration and precedent analysis. The primary objective of this research is to investigate the application of therapeutic architectural principles in the design of retreat house complexes. The methodology is structured as follows: (1) conducting a comprehensive literature review; (2) elaborating relevant references on therapeutic concepts and retreat house design through ideogram representation; (3) analyzing the outcomes of this elaboration concerning selected case studies; and (4) formulating conclusions. The findings of the study reveal a strong correlation between the architectural design of retreat houses and the implementation of therapeutic concepts, suggesting that such integration is instrumental in enhancing the restorative function of these spaces.